Twelve-Year Follow-Up of Laser Frenectomy during Early Mixed Dentition - Elhadi Mohieldin Awooda (Case Reports in Dentistry)
Median maxillary labial frenum (MMLF) is one of the oral freni, found on the inner side of the centre of the upper lip. Maxillary midline diastema (MMD) is commonly associated with highly attached frenum, and frenectomy during early mixed dentition is controversial. A 6-year-old boy came with a chief complaint of unpleasant spacing between the two upper front teeth. A median maxillary high attached labial frenum with midline spacing of 5 mm was diagnosed. A consensus was made with the child’s father to remove the frenum by laser. Diode laser frenectomy was done, and subsequent follow-up for 12 years revealed no relapse and complete closure of the diastema. Frenectomy during early mixed dentition could be a suitable option for the closure of midline diastema.